Reinforced concrete building design project & project based learning / Anis Balqis Irdina Jamal Nasir - Jamal Nasir, Anis Balqis Irdina (2022)
In preparation of this report, students need to search for a complete architectural drawing according to the Uniform Building By-Laws, UBBL (1994). After the drawing has been obtained, student are required to prepare a project schedule by using Microsoft Project software. The function of preparing a project schedule is to estimate the time to complete the construction project. Therefore, from the project schedule that has been prepared, the estimated time take for this project to complete is 168 days. After that, from the architectural drawing, we prepared a structural key plan for the house that consists of ground floor plan, first floor plan and roof plan by using AutoCAD. We proceed with calculating the permanent action and also variable action for each slab on each floor so that we can start with our designing. From the structural key plan, student are able to designing building structure such as slab, simply supported beam, continuous beam, column, pad footing and staircase. We are required to do a manual calculation and also a software calculation by using PROKON. Following this, we are able two compare the value that we have obtained from manual calculation with the value that we obtained from PROKON. In the meantime, student are required to find a solution for two case study, which is the first case study is about soil bearing capacity and pad footing size, and the second case study is about flexible pavement design. Hence, the chosen flexible pavement design is full depth asphalt pavement.